2017
DOI: 10.21037/atm.2017.07.19
|View full text |Cite
|
Sign up to set email alerts
|

Sedation and neuromuscular blocking agents in acute respiratory distress syndrome

Abstract: Mechanical ventilation (MV) is the cornerstone of acute respiratory distress syndrome (ARDS) management. The use of protective ventilation is a priority in this acute phase of lung inflammation. Neuromuscular blocking agents (NMBAs) induce reversible muscle paralysis. Their use in patients with ARDS remains controversial but occurs frequently. NMBAs are used in 25-45% of ARDS patients for a mean period of 1±2 days. The main indications of NMBAs are hypoxemia and facilitation of MV. For ethical reasons, NMBA us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 89 publications
0
44
0
4
Order By: Relevance
“…[19][20][21][22] Studies also suggest decreased incidence of barotrauma and ventilator induced lung injury with the use of NMBAs. 8,21 However, all these authors had studied adult patients. Mortality in our study control group was 46.7% (14/30).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[19][20][21][22] Studies also suggest decreased incidence of barotrauma and ventilator induced lung injury with the use of NMBAs. 8,21 However, all these authors had studied adult patients. Mortality in our study control group was 46.7% (14/30).…”
Section: Discussionmentioning
confidence: 99%
“…6 Clinical practice in PARDS is mostly extrapolated from findings in adult studies and further research in stratification of management in PARDS is urgently required. 7 A review done in 2017 8 suggests that neuromuscular blocking agents (NMBAs) are used in 25 to 45% of ARDS patients for a mean period of 1 AE 2 days. However, role of neuromuscular blockade in the management of ARDS is still controversial.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether spontaneous respiration in ARDS is helpful or harmful remains an area of debate [8]. Clinical studies confirmed that sedation inhibits the driving of the respiratory center and reduces the amplitude of spontaneous respiration, especially for early moderate to severe ARDS, deep sedation and even muscle relaxation can greatly improve the prognosis of patients and reduce the incidence of VILI [9,10]. However, for mild ARDS or convalescent ARDS, it is recommended to keep spontaneous respiration, which may be more conducive to the recovery of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Las primeras publicaciones sobre BNM fueron reportes de casos que obtuvieron mejoría en la relación PaO 2 / FiO 2 . [13][14][15][16][17] Hasta donde es de nuestro conocimiento, se han publicado tres metaanálisis sobre el tema. [18][19][20] Sin embargo, en ninguno de los estudios previos se cita la evidencia más reciente.…”
Section: Introductionunclassified